2020
DOI: 10.3389/fimmu.2020.01956
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic Agents in Combination With Immune Checkpoint Inhibitors: A Promising Strategy for Cancer Treatment

Abstract: Advances in cancer immunity have promoted a major breakthrough in the field of cancer therapy. This is mainly associated with the successful development of immune checkpoint inhibitors (ICIs) for multiple types of human tumors. Blockade with different ICIs, including programmed cell death 1 (PD-1), programmed cell death-ligand 1 (PD-L1), and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) inhibitors, may activate the immune system of the host against malignant cells. However, only a subgroup of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 169 publications
4
145
0
Order By: Relevance
“…Indeed, VEGF and TGF-β signaling and abnormal vasculature, all belonging to the selected targets presented in this review has been implicated in fostering immunosuppression [ 398 ]. Their inhibition have been already shown to improved immunotherapies clinical outcomes in various cancer [ 399 ]. Although the impact of targeted therapies on iTME is still unclear, ongoing clinical trials combining bevacizumab or others targeted therapies to check-point inhibitors (for instance: NCT03743662, NCT03661723, NCT04704154) open new perspectives for GBM treatment.…”
Section: Discussion-guidance Towards Future Gbm Targeted Therapiesmentioning
confidence: 99%
“…Indeed, VEGF and TGF-β signaling and abnormal vasculature, all belonging to the selected targets presented in this review has been implicated in fostering immunosuppression [ 398 ]. Their inhibition have been already shown to improved immunotherapies clinical outcomes in various cancer [ 399 ]. Although the impact of targeted therapies on iTME is still unclear, ongoing clinical trials combining bevacizumab or others targeted therapies to check-point inhibitors (for instance: NCT03743662, NCT03661723, NCT04704154) open new perspectives for GBM treatment.…”
Section: Discussion-guidance Towards Future Gbm Targeted Therapiesmentioning
confidence: 99%
“…Angiogenesis involves many signaling pathways, such as vascular endothelial growth factor (VEGF)-VEGF receptor (VEGFR), platelet derived growth factor (PDGF)-PDGF receptor (PDGFR) and fibroblast growth factor (FGF)-FGF receptor (FGFR). These signaling pathways influence multiple steps of the cancer immune response ( 31 , 32 ) ( Figure 1 ). VEGF is one of the most studied factors triggering angiogenesis.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Angiogenic molecules are capable to regulate the expression of different adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM1) to inhibit the transfer of immune cells to TME ( 28 ). Moreover, tumor endothelial cells could not only form a specific selective barrier to inhibit the penetration of certain immune cells ( 31 ), but also modulate the activity and variability of immune cells to regulate immunosuppression ( 32 ).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…As the largest family of receptor tyrosine kinases (RTKs), the erythropoietin-producing hepatocellular carcinoma (Eph) receptors are involved in a wide range of physiological activities, especially tumorigenesis, tumor immunity, and tumor angiogenesis [13][14][15]. Tumor angiogenesis is associated with immunosuppression [16]. Recent clinical trials showed that combination therapy of anti-angiogenesis and ICIs achieved more favorable outcomes than monotherapy in different cancers [17][18][19].…”
Section: Introductionmentioning
confidence: 99%